Evaluation of disinfection methods for personal protective equipment (PPE) items for reuse during a pandemic - Archer, John; Mikelonis, Anne; Wyrzykowska-Ceradini, Barbara; Morris, Eric; Sawyer, Jonathan; Chamberlain, Timothy; Abdel-Hady, Ahmed; Monge, Mariela; Touati, Abderrahmane (PloS one, 2023)
The COVID-19 pandemic resulted in many supply chain issues, including crippling of essential personal protective equipment (PPE) needed for high-risk occupations such as those in healthcare. As a result of these supply chain issues, unprecedented crisis capacity strategies were implemented to divert PPE items such as filtering facepiece respirators (FFRs, namely N95s) to those who needed them most for protection. Large-scale methods for decontamination were used throughout the world to preserve these items and provided for their extended use. The general public also adopted the use of non-specialized protective equipment such as face coverings. So, the need for cleaning, decontamination, or disinfection of these items in addition to normal clothing items became a necessary reality. Some items could be laundered, but other items were not appropriate for washing/drying. To fill research gaps in small-scale, non-commercial cleaning and disinfection, this bench-scale research was conducted using small coupons (swatches) of multiple PPE/barrier protection materials inoculated with virus (non-pathogenic bacteriophages Phi6 and MS2) and tested against a range of decontamination methods including bleach-, alcohol- and quaternary ammonium compound (QAC)-based liquid sprays, as well as low concentration hydrogen peroxide vapor (LCHPV) and bench-scale laundering. In general, non-porous items were easier to disinfect than porous items, and the enveloped virus Phi6 was overall easier to inactivate than MS2. Multiple disinfection methods were shown to be effective in reducing viral loads from PPE coupons, though only laundering and LCHPV were effective for all materials tested that were inoculated with Phi6. Applications of this and follow-on full-scale research are to provide simple effective cleaning/disinfection methods for use during the current and future pandemics.